Effects of Ascorbic Acid on Diurnal Variations in Rectal Temperature of Shaver Brown Pullets During the Hot-Dry Season - Ayo, J.O.; Sinkalu, V.O. (International Journal of Poultry Science, 2007)
Experiments were performed with the aims of determining the fluctuation in rectal temperature (RT) of Shaver Brown pullets and the effect of vitamin C or Ascorbic Acid (AA) administration on the fluctuation during the hot-dry season in the Northern Guinea Savannah zone of Nigeria. The RT of 25 experimental and 25 control pullets were measured every hour from 06:00 to 19:00 hours for three days, three days apart, with a standard clinical thermometer. The experimental pullets were individually administered orally with AA in drinking water at the dose of 52 mg kg -1 dissolved in sterile water, while the control pullets were given only normal water, without AA addition. In experimental pullets, the lowest hourly RT of 41.0±0.1 °C was obtained at 06:00 hours, while the highest value of 41.6±0.0 °C was recorded at 14:00 and 15:00 hours (p